1978
DOI: 10.1007/bf00607445
|View full text |Cite
|
Sign up to set email alerts
|

A study of the calcium carbimide-ethanol interaction in man

Abstract: In six male alcoholic volunteers, oral administration of calcium carbimide (0.7 mg/kg) before ingestion of ethanol (0.5 g/kg) produced an interaction consisting of increased blood acetaldehyde level, tachycardia and increased pulse pressure, which was due mainly to decreased diastolic blood pressure. For these experimental conditions, calcium carbimide had a duration of action of at least 24 h to produce an interaction with ethanol. The order of intensity of the interaction with regard to the calcium carbimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The combined effect of a smaller distribution volume and a decrease in slope resulted in a statistically significant retardation of ethanol elimination from the body (P < 0.001). This supports the work of Brien et al (1978Brien et al ( , 1979 who investigated the effect of dose of ethanol and time of administration relative to CC pretreatment on the efficacy of the drug-alcohol flush reaction. These workers showed a slower elimination of ethanol when CC was given 4 h before drinking.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The combined effect of a smaller distribution volume and a decrease in slope resulted in a statistically significant retardation of ethanol elimination from the body (P < 0.001). This supports the work of Brien et al (1978Brien et al ( , 1979 who investigated the effect of dose of ethanol and time of administration relative to CC pretreatment on the efficacy of the drug-alcohol flush reaction. These workers showed a slower elimination of ethanol when CC was given 4 h before drinking.…”
Section: Discussionsupporting
confidence: 85%
“…The concentration-time profiles of ethanol and acetaldehyde measured in breath resemble those reported earlier involving direct determinations in specimens of plasma and whole blood (Brien et al, 1978;. Good correlations between breath acetaldehyde and free plasma concentrations were recently demonstrated during the drug-alcohol flush reaction (Stowell et al, 1984).…”
Section: Discussionsupporting
confidence: 74%
“…and there are positive, linear correlations between blood acetaldehyde level and heart rate in individuals for this interaction. 3,4 In view of this it is interesting that for subject 3 the blood acetaldehyde level increased to the greatest extent in experiment 3, with a peak level of 7.94 ILg/ml ( Fig. 2 and Table II), but the heart rate increase was largest in experiment 1, with a peak heart rate of 137 bpm ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…3 There is, however, appreciable interindividual variability in the intensity and the duration of the CC-ethanol interaction. :': 4 Because CC has a rapid onset of action (I hr)" it could be administered only when required by the patient, i.e., before a potential drinking situation. Obviously, such an individual must be responsible, motivated, and well aware of typical events that precede drinking situations.…”
mentioning
confidence: 99%
“…It interferes with the metabolism of alcohol through non-competitive inhibition of aldehyde dehydrogenase;' increased hepatic and blood acetaldehyde levels result when ethanol has also been ingested. 2 In man the relatively high blood levels of acetaldehyde induce an aversive situation, which appears synchronously with the ingestion of alcohol, it being the alcohol itself which is manifested as a series of unpleasant organic responses e.g. tachycardia, hypotension, facial flushing, that is usually sufficient to deter d r i n k i r~g .~.~ Although the pharmacological activity of cyanamide is well known, there are few references in the literature to its disposition and p h a r m a c o k i n e t i c~.~,~~~ Recently, a pharmacokinetic profile of cyanamide in rat after oral administration of calcium cyanamide was reported by Loomis and Brien,' who showed that the apparent elimination half-life of cyanamide is 92.4 min and that the maximal plasma cyanamide level is achieved 1 hour after oral administration.…”
Section: Introductionmentioning
confidence: 97%